Televisi dan Fenomena Kekerasan Perspektif Teori Kultivasi - Yuliati, Nova (Mediator, 2005)
TV violence becomes one of the main polemics nowadays. Communication experts, media activists, and parents are strongly opposed and debated bad TV content due to its effect on children’s aggressive behavior. As stated by George Gerbner, communication expert who theorized Cultivation Theory, TV power comes from the symbolic content of the real-life drama shown hour per hour, week after week. Furthermore, television is easy to access and relatively cheap. More than 90 percent residents watch TV everyday. Cultivation theory theorized by Gerbner recently has developed and gave birth many other theories such as mainstreaming, resonance, desensitization, and priming.